Advanced mycelium materials as potential self-growing biomedical scaffolds - Maria Elena Antinori (Nature Portfolio, 2021)
Abstract Mycelia, the vegetative part of fungi, are emerging as the avant-garde generation of natural, sustainable, and biodegradable materials for a wide range of applications. They are constituted of a self-growing and interconnected fibrous network of elongated cells, and their chemical and physical properties can be adjusted depending on the conditions of growth and the substrate they are fed upon. So far, only extracts and derivatives from mycelia have been evaluated and tested for biomedical applications. In this study, the entire fibrous structures of mycelia of the edible fungi Pleurotus ostreatus and Ganoderma lucidum are presented as self-growing bio-composites that mimic the extracellular matrix of human body tissues, ideal as tissue engineering bio-scaffolds. To this purpose, the two mycelial strains are inactivated by autoclaving after growth, and their morphology, cell wall chemical composition, and hydrodynamical and mechanical features are studied. Finally, their biocompatibility and direct interaction with primary human dermal fibroblasts are investigated. The findings demonstrate the potentiality of mycelia as all-natural and low-cost bio-scaffolds, alternative to the tissue engineering systems currently in place.